The Directive 2016/97 On Insurance Distribution (IDD) And Private International Law - Fras, Mariusz (Review of European and Comparative Law, 2019)
Clear normative grounds for the information obligation are visible in the Directive (EU) 2016/97 of the European Parliament and of the Council of 20 January 2016 on insurance distribution (hereinafter: IDD). One of the challenges before insurance law is to answer the question whether and how one should sanction violations of disclosure obligations resulting in the absence of the desired insurance protection. In this aspect important legal problem is law applicable to the assessment of liability for violation of disclosure obligations by the insurer. The second important problem is law applicable to the assessment of liability for violation of disclosure obligations by third parties vis-a-vis the insurer. Some remarks concerning jurisdiction in matters relating to the loss of chance to become insured, have different practical implications.